Hepatoprotective Activities of Seed Extract and Fractions of Telfairia occidentalis on Doxorubicin-Induced Hepatotoxicity in Rats - Ugochi Queenette Nwosu; Chinyelu C. Osigwe; Ugonma Florence Uwaeme; Unyime A. Fabian; Jude Efiom Okokon (Biology, Medicine, & Natural Product Chemistry, 2025)
Telfairia occidentalis Hook (cucurbitaceae) seeds, which is used in the preparation of soups and as medicine traditionally to treat various diseases by the Ibibios was investigated for effect against doxorubicin-induced hepatotoxicity. The seed extract (138 -553 mg/kg) and fractions; dichloromethane (DCM) and aqueous, 276 mg/kg) were evaluated for hepatoprotective activity against doxorubicin-induced liver injury in rats. Liver function parameters, liver oxidative stress markers and liver histology were used to assess the liver protective potential of the extract and fractions. The seed extract and fractions significantly (p<0.05-0.01) reduced the serum levels of AST, ALT, ALP, total and direct bilirubin that were elevated by doxorubincin. Also, the reduced levels of total protein and albumin by doxorubicin were increased by the extract coadministration. The levels of GSH, GST, SOD, GPx, and CAT that were decreased by doxorubicin were significantly (p<0.01) elevated and raised MDA level was reduced by the seed extract and fractions. Histology of the liver sections of extract -treated animals showed reductions in the pathological features compared to the organotoxic-treated animals. The chemical pathological changes were consistent with histopathological observations suggesting marked hepatoprotective potential. The anti-toxic effect of this plant may in part be mediated through the chemical constituents of the plant. The seeds of Telfairia occidentalis possess anti-toxicant properties which can be exploited in the treatment of doxorubicin related toxicities.